Penerapan Model Pembelajaran Elaborasi Dalam Meningkatkan Hasil Belajar IPA Siswa Smp Negeri 3 Mazo Tahun Pelajaran 2024/2025 - Eliaman Hulu (Program Studi Pendidikan Biologi - Universitas Nias, 2025)
The low mathematics learning outcomes at SMP Negeri 3 Mazo are caused by the dominance of conventional learning models that result in passive students, difficulty understanding the material, and learning outcomes below the Minimum Completion Criteria (KKM). The purpose of this study is to describe the improvement in the quality of the mathematics learning process and outcomes through the application of the Elaboration learning model. Classroom Action Research (CAR) was carried out in two cycles in the even semester of the 2024/2025 academic year, with 25 students of class VIII-1 as subjects. Each cycle consisted of planning, action, observation, and reflection. Data collection instruments included student and teacher activity observation sheets, learning outcome tests, learning quality questionnaires, interviews, and documentation. Data were analyzed descriptively quantitatively. The results showed that the percentage of the quality of the learning process increased from 67% (sufficient category) in cycle I to 85% (good category) in cycle II. The average learning outcomes increased significantly from 66.02 (sufficient) with classical completeness of 60% in cycle I, to 89.10 (good) with completeness of 100% in cycle II. These findings confirm that the Elaboration model is effective in encouraging students to explore information, develop deeper understanding, and retain material more meaningfully. Therefore, this model is recommended as an alternative for student-centered mathematics learning.